Epidermal growth factor receptor as a predictor of tumor response to preoperative chemoradiation in locally advanced gastric carcinoma - Sirak, Igor; Petera, Jiri; Hatlova, Jana; Vosmik, Milan; Melichar, Bohuslav; Dvorak, Josef; Zoul, Zdenek; Tycova, Vera; Lesko, Michal; Hajduch, Marian (Strahlentherapie und Onkologie, 2008)
PURPOSE: The purpose of our study was a retrospective evaluation whether the intensity of epidermal growth factor receptor (EGFR) expression predicts tumor response to preoperative chemoradiotherapy in patients with locally advanced gastric carcinoma. PATIENTS AND METHODS: Thirty-six patients with gastric adenocarcinoma (cT2-4 or N+) were studied. Preoperative treatment consisted of 30-45 Gy of gastric irradiation with continuous 5-fluorouracil and weekly cisplatin. Surgical resection was performed 4-6 weeks later. EGFR expression in pretreatment tumor biopsies was assessed by immunohistochemistry. Level of EGFR expression was determined from the intensity and extent of staining. Tumor response was defined as a reduction of at least one T-stage level and/or finding of intense tumor regression in histopathologic examination. RESULTS: Seventeen patients responded to preoperative chemoradiation -- 8 patients (22%) had pathologic complete response, 9 patients (25%) were downstaged. Positive EGFR expression was found in 8 tumors (22%), and represented a significant predictive marker of poor tumor response in multivariate logistic regression analysis (p = 0.015). Response to chemoradiotherapy was found in 60% (16/28) of EGFR negative patients and in 13% (1/8) of EGFR positive patients (p = 0.044). None of the eight EGFR positive patients achieved pathologic complete response in comparison with 8/28 (29%) of patients with EGFR negative staining (p = 0.16). CONCLUSION: EGFR may represent a molecular marker predictive for poor response to preoperative chemoradiotherapy in locally advanced gastric carcinoma.
Keywords: nádory žaludku; Adenocarcinoma; kombinovaná terapie; gastrektomie; Humans; fluoruracil; cisplatina; Gastrectomy; Cisplatin; ErbB Receptors; Predictive Value of Tests; Radiotherapy Dosage; protokoly protinádorové kombinované chemoterapie; celková dávka radioterapie; výsledek terapie; lidé; erbB receptory; staging nádorů; prediktivní hodnota testů; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Fluorouracil; předoperační péče; adenokarcinom; Neoplasm Staging; Combined Modality Therapy; Preoperative Care; Stomach Neoplasms